Unplanned Reoperation Rate at a Government-Designated Regional Trauma Center in Gangwon Province - Minju Kim; Seongyup Kim (Journal of Trauma and Injury)
Purpose Determining appropriate ways to assess health care quality within the National Health Insurance System is of interest to both the Korean government and the medical community. However, in the trauma field, the number of indicators used to evaluate surgical quality is limited. Using data collected over 5 years at Wonju Severance Christian Hospital Trauma Center in Korea, this study aimed to determine whether the unplanned reoperation rate in the field of trauma surgery could be used to assess the quality of an institution’s surgical care. Methods In total, 665 general surgical procedures were performed at the Trauma Center in 453 patients with abdominopelvic injuries from January 2015 to December 2019. Data were collected from the Trauma Center’s data registry and medical records, and included information regarding patients’ demographic characteristics, the type of index operation, and the reason for unplanned reoperations. Results A total of 453 index operations were evaluated. The proportion of patients with an Injury Severity Score (ISS) >15 was 48–70% over the 5-year period, with an unplanned reoperation rate of 2.1–9.3%. Patients had an average ISS score of 17.5, while the average Abbreviated Injury Scale score was 2.87. Unplanned reoperations were required in about 7% of patients. The most common complications requiring reoperation were recurrent bleeding (26.9%), wound problems (26.9%), intestinal infarction (15.4%), and anastomosis site leakage (7.7%). The procedures most frequently requiring unplanned reoperations were bowel surgery (segmental resection, primary repair, enterostomy, etc.) (24.5%) and preperitoneal pelvic packing (10.6%). Conclusions The proportion of reoperations was confirmed to be affected by injury severity.